Portrait of the Filipino as an outstanding private school administrator - Lahoz, Elizabeth Q. (2005)
The purpose of this study was to identify the qualities of outstanding Filipino private school administrators and the factors contributory to their outstanding leadership. Qualitative research design was used. The respondents were selected purposively in a multiple sampling of three--the Delphi response group, the nominators, and the nominees. The findings revealed 22 qualities of outstanding administrators as drawn up by the Delphi Response Group. The qualities were grouped as Leadership Abilities, People Skills, Management Competencies, and Personal Values.